Perancangan Hovercraft Pengangkut Sistem Desalinasi Untuk Pelayaran Jarak Dekat Antar Pulau - Taufan Prasetyo; Misbakhul Fatah; Ike Dayi Febriana (Politeknik Negeri Madura, 2020)
Indonesia is an archipelago country which consist of several large islands and thousands of small islands. According to the latest data, a total of 17.504 islands exist in Indonesian, which 6.000 are inhabited islands. Small islands with an area of ??less than 2.000 m2 do not have sufficient clean water sources or even none at all. Many solutions have been developed regarding the clean water crisis, which one is to provide a distilling seawater into clean water or what the local government calls the desalination system. However, it did not work effectively because the cost of equipments maintenance was quite expensive. In this study, a water transportation for distributing portable desalination machines or systems and other logistical needs between island is designed. Due to the lack of adequate docks and loading facilities on many islands, the researchers took the initiative to design a Hovercraft, an Amphibious Ship to simplify the distribution and loading process on land. The design process is carried out using the sister ship method by considering the size of the object to be distributed so that the length = 13.2 m, Width = 6.7 m, Aluminum material, with a total weight = 19 tons, Speed ??= 50 knots, and the design refers to the Carrier type of Hovercraft. Based on these data, the total lifting capacity is 1909.44 HP and the thrust is 695.61 HP.